Graphitized nanocarbons cages containing boron element and carbon-based catalysts, and methods of preparation and use

CN116654910BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310163630.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-02-25
Filing Date
2023-02-24
Publication Date
2026-10-16
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

[0003]目前燃料电池中铂碳催化剂(Pt/C)是使用最广泛的催化剂,商业上通过化学还原法把浸渍在Vulcan XC-72碳黑内部和表面的氯铂酸还原成铂纳米颗粒,制备出的40%Pt/C催化剂,其在使用过程中由于铂溶解和团聚而造成的铂表面积的明显下降,大大影响了铂碳催化剂的寿命

Benefits of technology

[0020] Using boron-doped graphitized carbon nanocages with a specific diameter and a boron atom molar percentage of 10-30% as a support, as provided in this invention, carbon-based catalysts containing platinum are prepared, which is beneficial to improving the oxygen reduction reaction (ORR) activity and mass specificity activity of fuel cell catalysts (Pt/C catalysts).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116654910B_ABST
    Figure CN116654910B_ABST
Patent Text Reader

Abstract

The present application relates to the field of carbon materials, and discloses a graphitized nanometer carbon cage containing boron elements, a carbon-based catalyst, and a preparation method and application, wherein the graphitized nanometer carbon cage containing boron elements has a hollow cage structure with a diameter of 2-100 nm, and the boron atomic mole percentage detected by XPS is 10-30%. The graphitized nanometer carbon cage doped with boron and provided by the present application has a specific diameter and a boron atomic mole percentage of 10-30%, and the carbon-based catalyst containing metal platinum prepared by using the graphitized nanometer carbon cage as a carrier is beneficial to improving the activity of the oxygen reduction reaction of a fuel cell catalyst (Pt / C catalyst).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of carbon materials technology, specifically to graphitized carbon nanocages containing boron and carbon-based catalysts, as well as their preparation methods and applications. Background Technology

[0002] A fuel cell is a power generation device that converts the chemical energy of fuel into electrical energy directly through an electrochemical reaction without combustion. It has advantages such as high energy density, fast start-up, and high energy conversion efficiency, and is considered one of the most promising power generation technologies.

[0003] Currently, platinum-carbon catalysts (Pt / C) are the most widely used catalysts in fuel cells. Commercially, 40% Pt / C catalysts are prepared by reducing chloroplatinic acid impregnated inside and on the surface of Vulcan XC-72 carbon black into platinum nanoparticles via chemical reduction. However, during use, the significant decrease in platinum surface area due to platinum dissolution and agglomeration greatly affects the lifespan of the Pt / C catalyst. Therefore, developing catalysts with high catalytic activity and stability is of great value for reducing costs and promoting the practical application of fuel cell technology.

[0004] Nanocarbon cages are hollow carbon nanomaterials coated with graphite layers. Their surface structure is similar to that of porous carbon, with pore sizes ranging from 2 to 100 nm and generally large specific surface areas. Due to their low density, high specific surface area, unique porous structure, strong corrosion resistance, and good electrical conductivity, they have been found to have exceptionally good application prospects as catalyst supports in recent years, attracting extensive research.

[0005] By doping and modifying carbon materials to introduce defect sites or heteroatom functional groups, the local charge distribution can be altered, enabling effective adsorption of metal ions and serving as a support for noble metal catalysts, thereby enhancing their catalytic activity. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems of low mass-to-specific-activity of Pt / C catalysts in the prior art, and to provide a graphitized carbon nanocage containing boron, a carbon-based catalyst, a preparation method, and applications. Using the graphitized carbon nanocage containing boron provided by this invention as a support, combined with the noble metal platinum, the catalytic activity of the catalyst can be improved.

[0007] During their research, the inventors of this invention discovered that boron atoms have an atomic radius similar to that of carbon atoms, and can be used as electron donors to dope into nano-carbon cage materials. The boron atoms introduced onto the surface can have a corresponding impact on the graphitic carbon structure, and with further increases in processing temperature, the doping state of the boron atoms also changes, significantly enhancing the alteration of the catalyst material properties.

[0008] To achieve the above objectives, the present invention provides a graphitized carbon nanocage containing boron, wherein the graphitized carbon nanocage containing boron has a hollow cage-like structure with a diameter of 2-100 nm, preferably 2-50 nm, and more preferably 5-30 nm, and the boron atom molar percentage content measured by XPS is 10-30%.

[0009] Preferably, the graphitized carbon nanocage also contains nitrogen, with the nitrogen atom molar percentage measured by XPS being 0.5-10%.

[0010] Preferably, the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the graphitized carbon nanocage, as determined by X-ray photoelectron spectroscopy, is greater than 70%, and more preferably greater than 80%.

[0011] A second aspect of this invention provides a method for preparing graphitized carbon nanocages containing boron, the method comprising the following steps:

[0012] (1) Provide a solution containing a transition metal salt, a carbon source and a solvent, and then dry it to obtain a precursor;

[0013] (2) Under an inert or reducing atmosphere, the precursor obtained in step (1) is subjected to high-temperature pyrolysis at a temperature of 850-1300℃ to obtain pyrolysis products.

[0014] (3) The pyrolysis product is acid washed, then solid-liquid separation and drying are performed to obtain nano-carbon cages;

[0015] (4) The nano carbon cage is mixed with a boron source and then subjected to high-temperature treatment at 300-1500℃.

[0016] A third aspect of the present invention provides a carbon-based catalyst containing platinum, the catalyst comprising a support and platinum supported on the support, wherein the support contains graphitized carbon nanocages containing boron as described in the first aspect or graphitized carbon nanocages containing boron prepared by the preparation method described in the second aspect.

[0017] A fourth aspect of this invention provides a method for preparing a carbon-based catalyst containing platinum, the method comprising:

[0018] After mixing the support with a platinum source in the presence of a solvent, a carbon-based catalyst containing platinum is obtained by liquid-phase reduction or gas-phase reduction; the support contains either the graphitized carbon nanocage containing boron as described in the first aspect or the graphitized carbon nanocage containing boron prepared by the method described in the second aspect.

[0019] The fifth aspect of the present invention provides the application of the platinum-containing carbon-based catalyst described in the third aspect or the platinum-containing carbon-based catalyst prepared by the method described in the fourth aspect in a fuel cell.

[0020] Using boron-doped graphitized carbon nanocages with a specific diameter and a boron atom molar percentage of 10-30% as a support, as provided in this invention, carbon-based catalysts containing platinum are prepared, which is beneficial to improving the oxygen reduction reaction (ORR) activity and mass specificity activity of fuel cell catalysts (Pt / C catalysts). Attached Figure Description

[0021] Figure 1 This is a TEM image of the boron-doped carbon nanocage prepared in Example A-1;

[0022] Figure 2 This is the XPS B1s image of the boron-doped carbon nanocage prepared in Example A-1;

[0023] Figure 3 This is the BJH pore size distribution curve of the boron-doped carbon nanocage prepared in Example A-1;

[0024] Figure 4 This is a TEM image of the platinum-supported catalyst prepared in Example A-1;

[0025] Figure 5 This is a TEM image of the boron-nitrogen-doped carbon nanocages prepared in Example B-1;

[0026] Figure 6 This is the XPS B1s image of the boron-doped carbon nanocage prepared in Example B-1;

[0027] Figure 7 This is the XPS N1S image of the boron-doped carbon nanocage prepared in Example B-1;

[0028] Figure 8 This is a TEM image of the platinum-supported catalyst prepared in Example B-1. Detailed Implementation

[0029] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0030] The first aspect of the present invention provides a graphitized carbon nanocage containing boron, wherein the graphitized carbon nanocage containing boron has a hollow cage-like structure with a diameter of 2-100 nm, preferably 2-50 nm, more preferably 5-30 nm, and the boron atom molar percentage content measured by XPS is 10-30%, for example 10, 12, 15, 17, 20, 22, 25, 27, 30%, and any value within any range of any two of these values.

[0031] In this invention, the surface morphology of the material is characterized by high-resolution transmission electron microscopy (HRTEM). The HRTEM used is a JEM-2100 (Japan Electronics Corporation), and the HRTEM testing conditions are: accelerating voltage of 200 kV. The diameter of the nano-carbon cage can be measured from the HRTEM images.

[0032] In this invention, X-ray photoelectron spectroscopy analysis was performed on an ESCALab250 X-ray photoelectron spectrometer from Thermo Scientific equipped with ThermoAvantage V5.926 software. The excitation source was monochromatic AlKα X-rays with an energy of 1486.6 eV and a power of 150 W. The transmission energy used for narrow scanning was 30 eV, and the baseline vacuum during analysis was 6.53 × 10⁻⁶. -9 mbar, electron binding energy was corrected using the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and quantitative analysis was performed using the sensitivity factor method in the analysis module.

[0033] In this invention, the BET test method is as follows: the pore structure properties of the sample are determined by a Quantachrome AS-6B analyzer, and the mesopore distribution curve is calculated from the desorption curve using the Barrett-Joyner-Halenda (BJH) method.

[0034] In this invention, the degree of graphitization of graphitized carbon nanocages is characterized by Raman spectroscopy at 1355 cm⁻¹. -1 The peak (D peak) is attributed to structural defects, consisting of amorphous carbon, at 1585 cm⁻¹. -1 The peak (G peak) is attributed to carbon in a planar structure. I0 is typically used. D / I G The degree of graphitization of a material is characterized by the intensity ratio of the D peak to the G peak. D / I GThe higher the value, the more defects and the lower the degree of graphitization. The Raman spectrum of the material was obtained using an RM2000 microconfocal Raman spectrometer (Reinshaw product). Technical specifications: The excitation source was a He-Ne laser with a wavelength of 525 nm.

[0035] In this invention, the hollow cage shape has the conventional interpretation in the art, specifically referring to a hollow sphere or quasi-sphere formed by a graphitized carbon layer surrounding it.

[0036] In this invention, the term "mesopore" is defined as a pore with a diameter in the range of 2-50 nm.

[0037] In this invention, the term "graphitized carbon nanocage containing boron" can also be called "boron-doped graphitized carbon nanocage". Specifically, the term refers to boron in various forms that are formed in the graphitized carbon nanocage during the preparation process.

[0038] Preferably, the boron-containing graphitized carbon nanocage has two or more mesoporous distribution peaks. More preferably, the first most probable pore size of the boron-containing graphitized carbon nanocage is 2-5 nanometers, for example, 2, 3, 4, 5 nanometers, and any value within the range formed by any two of these values; the corresponding second most probable pore size is 10-30 nanometers, for example, 10, 15, 20, 25, 30 nanometers, and any value within the range formed by any two of these values.

[0039] Preferably, in the Raman curve of the graphitized carbon nanocage containing boron, I D / I G The value is less than 1.2, preferably less than 1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or 0.9, and any value within the range formed by any two of these values. The graphitized carbon nanocage containing boron provided by this invention has obvious D peaks and G peaks, and has a certain degree of graphitization.

[0040] According to a preferred embodiment of the present invention, the molar content of carbon on the surface of the graphitized carbon nanocage containing boron, as measured by X-ray photoelectron spectroscopy, is 20-80%, for example 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75 or 80%, and any value within any range of any two of these values; the molar content of boron is 10-30%, for example 10, 15, 20, 25 or 30%, and any value within any range of any two of these values; and the molar content of oxygen is 5-50%, for example 5, 10, 15, 20, 25, 30, 35, 40, 45, 50%, and any value within any range of any two of these values.

[0041] The oxygen element in the graphitized carbon nanocage can be oxygen element that exists in various forms formed in the graphitized carbon nanocage.

[0042] According to a preferred embodiment of the present invention, the graphitized carbon nanocage containing boron is composed of carbon, oxygen and boron, and the molar content of carbon on the surface of the graphitized carbon nanocage containing boron is 20-80%, the molar content of boron is 10-30%, and the molar content of oxygen is 5-50%, as determined by X-ray photoelectron spectroscopy; preferably, the molar content of carbon is 33-70%, the molar content of boron is 12-30%, and the molar content of oxygen is 18-37%.

[0043] According to a preferred embodiment of the present invention, the thickness of the boron-containing graphitized carbon nanocage is 1-10 layers of graphitized carbon atoms, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10, and any value within the range formed by any two of these values. The thickness of the boron-containing graphitized carbon nanocage is observed by high-resolution transmission electron microscopy (HRTEM).

[0044] According to a preferred embodiment of the present invention, the graphitized carbon nanocage further contains nitrogen. There is no particular limitation on the form in which nitrogen exists. When the graphitized carbon nanocage also contains nitrogen, the graphitized carbon nanocage can be referred to as a "graphitized carbon nanocage containing boron and nitrogen" or a "boron-nitrogen-doped graphitized carbon nanocage," specifically referring to boron and nitrogen elements present in various forms within the graphitized carbon nanocage during its preparation process.

[0045] Preferably, the molar percentage of nitrogen atoms measured by XPS is 0.5-10%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10%, and any value within the range formed by any two of these values. More preferably, the molar percentage of nitrogen atoms measured by XPS is 0.5-1%.

[0046] Preferably, the molar content of carbon on the surface of the graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is 20-80%, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80%, and any value within any range of any two of these values; the molar content of nitrogen is 0.5-10%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10%, and any value within any range of any two of these values; the molar content of oxygen is 5-50%, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50%, and any value within any range of any two of these values; and the molar content of boron is 10-30%, for example, 10, 15, 20, 25, 30%, and any value within any range of any two of these values.

[0047] More preferably, the molar content of carbon on the surface of the graphitized carbon nanocage, as determined by X-ray photoelectron spectroscopy, is 30-70%, the molar content of nitrogen is 0.5-2%, the molar content of oxygen is 15-40%, and the molar content of boron is 12-29%.

[0048] According to a preferred embodiment of the present invention, the graphitized carbon nanocage containing boron is composed of carbon, oxygen, nitrogen and boron, and X-ray photoelectron spectroscopy shows that the molar content of carbon on the surface of the graphitized carbon nanocage is 30-70%, the molar content of nitrogen is 0.5-2%, the molar content of oxygen is 15-40%, and the molar content of boron is 12-29%.

[0049] According to the present invention, preferably, the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the graphitized carbon nanocage, as determined by X-ray photoelectron spectroscopy, is greater than 70%, and more preferably greater than 80%.

[0050] In a preferred embodiment, based on the total molar amount of nitrogen, X-ray photoelectron spectroscopy measures the molar content of pyrrole nitrogen in the nitrogen on the surface of the graphitized carbon nanocage to be 70-100%, for example, 70, 75, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99 or 100%, and the molar content of pyridine nitrogen is 0-30%, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 20, 25 or 30%.

[0051] Graphitized carbon nanocages with the above-mentioned preferred specific content of pyrrole nitrogen and / or pyridine nitrogen molar content and specific element composition are more conducive to improving the oxygen reduction reaction (ORR) activity of fuel cell catalysts (Pt / C catalysts).

[0052] In this invention, the terms "pyrrole nitrogen," "pyridine nitrogen," "graphite nitrogen," and "oxidized nitrogen" have their conventional meanings in the art, specifically referring to: pyridine nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 398.7-399.1 eV in X-ray photoelectron spectroscopy; pyrrole nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 398.8-400.2 eV in X-ray photoelectron spectroscopy; graphite nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 401.2-401.8 eV in X-ray photoelectron spectroscopy; and oxidized nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 402.8-403.6 eV in X-ray photoelectron spectroscopy.

[0053] A second aspect of this invention provides a method for preparing graphitized carbon nanocages containing boron, the method comprising the following steps:

[0054] (1) Provide a solution containing a transition metal salt, a carbon source and a solvent, and then dry it to obtain a precursor;

[0055] (2) Under an inert or reducing atmosphere, the precursor obtained in step (1) is subjected to high-temperature pyrolysis to obtain pyrolysis products;

[0056] (3) The pyrolysis product is acid washed, then solid-liquid separation and drying are performed to obtain nano-carbon cages;

[0057] (4) The nano carbon cage is mixed with a boron source and then subjected to high-temperature treatment at 300-1500℃.

[0058] The method for preparing boron-containing graphitized carbon nanocages provided by this invention involves doping with boron in the final step to obtain graphitized carbon nanocages with a specific boron content. When used in carbon-based catalysts containing platinum, this method is beneficial for improving the performance of platinum-containing carbon-based catalysts.

[0059] According to the present invention, preferably, the carbon source is a nitrogen-free organic polybasic acid and / or a nitrogen-containing carbon source (preferably a nitrogen-containing organic carboxylic acid). Particularly preferably, the nitrogen-free organic polybasic acid is at least one selected from citric acid, maleic acid, pyromellitic acid, terephthalic acid, and malic acid, more preferably citric acid; preferably, the nitrogen-containing carbon source is ethylenediaminetetraacetic acid. When the carbon source is a nitrogen-containing carbon source, it is understood that nitrogen will also be introduced into the graphitized carbon nanocage containing boron, and the resulting carbon nanocage will contain a specific molar amount of pyrrole nitrogen and / or pyridine nitrogen, giving the carbon nanocage particularly superior properties.

[0060] When the carbon source is a nitrogen-free organic polyacid, the amounts of the carbon source, transition metal salt, and boron source are such that, as measured by X-ray photoelectron spectroscopy, the molar content of carbon on the surface of the graphitized carbon nanocage is 20-80%, for example, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80%, and any value within any two of these values; the molar content of boron is 10-30%, for example, 10, 15, 20, 25, or 30%, and any value within any two of these values; and the molar content of oxygen is 5-50%, for example, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50%, and any value within any two of these values.

[0061] Preferably, the carbon source is a nitrogen-containing carbon source, and the amounts of the carbon source, transition metal salt, and boron source are such that, as measured by X-ray photoelectron spectroscopy, the molar content of carbon on the surface of the graphitized carbon nanocage is 20-80%, the molar content of nitrogen is 0.5-10%, the molar content of oxygen is 5-50%, and the molar content of boron is 10-30%. More preferably, the molar content of carbon on the surface of the graphitized carbon nanocage is 30-70%, the molar content of nitrogen is 0.5-2%, the molar content of oxygen is 15-40%, and the molar content of boron is 12-29%. More preferably, the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is greater than 70%, preferably greater than 80%.

[0062] Preferably, the transition metal salt is selected from at least one of organic acid salts, carbonates, and basic carbonates of transition metals; more preferably, the organic acid salt of the transition metal is an organic carboxylate salt of the transition metal that does not contain heteroatoms, preferably an acetate.

[0063] Preferably, the transition metal is at least one selected from iron, cobalt, nickel, and copper, and more preferably nickel.

[0064] According to some embodiments of the present invention, preferably, the transition metal salt is selected from basic nickel carbonate and / or nickel acetate.

[0065] According to a preferred embodiment of the present invention, in step (1), there is no particular limitation on the method of forming the solution. For example, the solution can be formed by heating, and more preferably by heating and stirring. The present invention also does not particularly limit the heating temperature and the stirring rate, as long as the solution can be formed.

[0066] According to a preferred embodiment of the present invention, preferably, in step (1), the precursor is obtained by dissolving a transition metal salt and a carbon source in a solvent to form a homogeneous solution, and then removing the solvent from the homogeneous solution (drying).

[0067] According to a preferred embodiment of the present invention, the molar ratio of the transition metal salt to the carbon source, calculated as transition metal element, is 1:0.5-1, more preferably 1:0.6-0.9. This preferred embodiment is more advantageous in improving the activity of the prepared nano-carbon cages when used as carbon-based catalysts.

[0068] The present invention does not particularly limit the type of solvent, as long as it can form a homogeneous solution. Preferably, the solvent is water and / or ethanol, more preferably water. The present invention also does not particularly limit the amount of solvent used, as long as it can form a homogeneous solution.

[0069] According to the method provided by the present invention, the temperature of the high-temperature pyrolysis is 850-1300℃, and more preferably 900-1200℃.

[0070] Preferably, in step (2), the high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 0.5-30℃ / min, preferably 1-20℃ / min, and even more preferably 5-10℃ / min, and then maintaining a constant temperature. A wide range of constant temperature time is available, taking into account both effectiveness and energy saving; the preferred constant temperature time is 20-600 min, more preferably 60-480 min.

[0071] According to a preferred embodiment of the present invention, in step (2), the temperature is raised to the high-temperature pyrolysis temperature in two stages, specifically: first, the temperature is raised to 400-800℃, preferably 500-700℃, at a rate of 1-20℃ / min, preferably 5-10℃ / min, and held at that temperature for 20-600min, preferably 60-480min; then, the temperature is raised to the high-temperature pyrolysis temperature at a rate of 1-20℃ / min, preferably 5-10℃ / min, and held at that temperature for 20-600min, preferably 60-480min.

[0072] According to some embodiments of the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon, and helium; and / or,

[0073] The reducing atmosphere is provided by hydrogen and optionally an inert gas, which is at least one of nitrogen, argon, neon, and helium. There is no particular limitation on the hydrogen content in the reducing atmosphere, which can be 1-100% by volume.

[0074] According to some embodiments of the present invention, in step (3), the pyrolysis product is acid-washed using an acid pickling agent. Specifically, the pyrolysis product is mixed with the acid pickling agent. The present invention does not have a particular limitation on the mixing method; it can be mixed by ultrasound or stirring. The acid pickling agent can be an acid conventionally used in the art, as long as it can remove the transition metals in the pyrolysis product. Preferably, the acid pickling agent is an aqueous solution of inorganic acid and / or an aqueous solution of organic acid, preferably at least one of aqueous solutions of hydrochloric acid, sulfuric acid, nitric acid, and citric acid, more preferably an aqueous solution of hydrochloric acid. Preferably, the concentration of the aqueous solution of inorganic acid and / or the aqueous solution of organic acid is 0.1-10 mol / L; the pH value of the acid pickling agent is less than 7. The present invention does not have a particular requirement for the amount of the acid pickling agent used, as long as it can remove the transition metals in the pyrolysis product.

[0075] According to some embodiments of the present invention, preferably, in step (3), the pickling temperature is 20-120°C, more preferably 60-100°C; and the time is 0.1-48h, more preferably 4-12h.

[0076] According to some embodiments of the present invention, in step (3), there is no particular limitation on the method of solid-liquid separation, and solid-liquid separation methods known in the art can be used, such as filtration.

[0077] Step (3) of the present invention preferably includes washing the solid product obtained from solid-liquid separation before the drying. The washing is used to remove acid and metal ions remaining on the nano-carbon cages during the acid washing process. Therefore, various water washing methods that can wash the nano-carbon cages to neutrality are applicable to the present invention.

[0078] According to some embodiments of the present invention, the drying is used to remove water from the carbon nanocages. The drying can be performed under normal pressure or reduced pressure. Drying conditions may include a temperature of 80-140°C and a time of 6-10 hours.

[0079] According to the method provided by the present invention, there is no particular limitation on the mixing method of the nano-carbon cage and the boron source in step (4). As long as the mixing is uniform, it can be carried out in the presence of a solvent and then dried, or it can be done by dry mixing and then grinding. There is no particular limitation on the specific mixing parameters, and those skilled in the art can make adaptive selections according to specific circumstances.

[0080] According to the method provided by the present invention, in step (4), the preferred high-temperature treatment temperature is 400-1200℃, for example, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃, 1200℃, and any value within the range formed by any two of these values. More preferably, the high-temperature treatment temperature is 450-1100℃.

[0081] Preferably, the high-temperature treatment time is 30-300 min, for example, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min, 300 min, and any value within the range formed by any two of these values.

[0082] The present invention offers a wide range of selectable heating rates for the high-temperature treatment, allowing those skilled in the art to make adaptive selections based on specific circumstances. This embodiment uses 5°C / min as an example for illustrative purposes, but the invention is not limited thereto.

[0083] The present invention has a wide range of choices for the type of boron source, as long as it can provide boron element in the nano carbon cage. Preferably, the boron source is selected from at least one of boric acid, boron oxide, ammonium borate and ammonium hydrogen borate.

[0084] Preferably, the amount of the nano-carbon cage and the boron source is such that the boron-containing graphitized nano-carbon cage obtained has a boron atom molar percentage content measured by XPS of 10-30%, preferably 12-30%.

[0085] A third aspect of the present invention provides a carbon-based catalyst containing platinum, the catalyst comprising a support and platinum supported on the support, wherein the support contains graphitized carbon nanocages containing boron as described in the first aspect or graphitized carbon nanocages containing boron prepared by the method described in the second aspect.

[0086] Preferably, based on the total amount of the carbon-based catalyst, the platinum mass percentage is 0.1-70%, more preferably 0.5-70%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70%, and any value within any range of any two of these values. More preferably, based on the total amount of the carbon-based catalyst, the platinum mass percentage is 30-50%.

[0087] A fourth aspect of this invention provides a method for preparing a carbon-based catalyst containing platinum, the method comprising:

[0088] After mixing the support with a platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction or gas-phase reduction; the support contains graphitized carbon nanocages containing boron as described in the first aspect or graphitized carbon nanocages containing boron prepared by the method described in the second aspect.

[0089] Preferably, the amount of support and platinum source used is such that, based on the total amount of the carbon-based catalyst, the mass percentage of platinum in the prepared catalyst is 0.1-70%, preferably 0.5-70%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70%, and any value within any range of any two of these values. More preferably, based on the total amount of the carbon-based catalyst, the mass percentage of platinum is 30-50%.

[0090] According to a preferred embodiment of the present invention, after mixing the support and platinum source in the presence of a solvent, the mixture is reduced to a carbon-based catalyst containing metallic platinum via liquid phase reduction, comprising:

[0091] The support and platinum source are mixed in the presence of a solvent, and the pH is adjusted preferably to 8-12 (e.g., 8, 9, 10, 11 or 12). A reducing agent is added for reduction, and then the mixture is dried (preferably washed before drying) to obtain a carbon-based catalyst containing metallic platinum.

[0092] In this preferred embodiment, preferably, the platinum source is at least one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, and other inorganic platinum salts.

[0093] Preferably, the platinum source is provided in the form of a solution, and its concentration is preferably 0.5 mol / L to 5 mol / L, for example 0.5, 1, 2, 3, 4 or 5 mol / L, and any value within any two of these values.

[0094] The present invention allows for a wide range of solvent selection; preferably, the solvent is water.

[0095] The pH is preferably adjusted using an alkaline solution, which may be a solution of one or more alkaline substances selected from sodium carbonate, potassium carbonate, ammonia, potassium hydroxide, and sodium hydroxide (preferably an aqueous solution).

[0096] In this preferred embodiment, the reducing agent is preferably selected from one or more of citric acid, ascorbic acid, formaldehyde, formic acid, ethylene glycol, sodium citrate, hydrazine hydrate, sodium borohydride, and glycerol.

[0097] In this preferred embodiment, the molar ratio of the reducing agent to the platinum source (calculated as Pt) is preferably between 2 and 100, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, and any value within the range formed by any two of these values.

[0098] In this preferred embodiment, the reduction temperature is preferably 50-150℃, for example 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150℃, and any value within any range formed by any two of these values. The reduction time is preferably 2-15h, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15h, and any value within any range formed by any two of these values.

[0099] In another preferred embodiment, the process of mixing the support and the platinum source in the presence of a solvent and then reducing them in the gas phase to obtain a carbon-based catalyst containing metallic platinum includes: mixing the support and the platinum source in the presence of a solvent, removing the solvent to obtain a precursor material, and then heat-treating the precursor material in a reducing atmosphere.

[0100] In this preferred embodiment, the heat treatment is preferably performed at 80-300°C (for example, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 220, 240, 260, 280, 300°C, and any value within the range formed by any two of these values) for 1-4 hours.

[0101] In this preferred embodiment, the platinum source is selected from at least one of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate, and platinum acetylacetonate.

[0102] The present invention has a wide range of solvents that can be selected. Preferably, the solvent is one or more of water, alcohol solvents and ketone solvents, and more preferably, the solvent is water and / or ethanol.

[0103] In this preferred embodiment, the mixture is further further comprising: allowing the mixed material to stand before removing the solvent, preferably for 10 hours or more, more preferably 15-48 hours. This method is more conducive to the loading of platinum and the full dispersion of Pt on the carrier surface.

[0104] In this preferred embodiment, the drying temperature during solvent removal is below 100°C.

[0105] In this preferred embodiment, the reducing atmosphere can be provided by hydrogen and optionally an inert gas (the selection range can be the same as the selection range described above), more preferably by a mixed atmosphere of hydrogen and nitrogen; preferably, the hydrogen content in the mixed atmosphere is 5-50% by volume.

[0106] The fifth aspect of this invention provides the application of the platinum-containing carbon-based catalyst described in the third aspect or the platinum-containing carbon-based catalyst prepared by the method described in the fourth aspect in fuel cells. The platinum-containing carbon-based catalyst provided by this invention is beneficial for improving the oxygen reduction reaction (ORR) activity of fuel cell catalysts and can be used as a support in fuel cell catalysts. Since this invention mainly relates to the improvement of catalysts, when applying the platinum-containing carbon-based catalyst of this invention to fuel cells, there are no particular limitations on other operating conditions and structures of the fuel cell; those skilled in the art can make appropriate selections based on the solid-state operating conditions.

[0107] The present invention will be described in detail below through embodiments.

[0108] Unless otherwise specified, all reagents used in this invention are of analytical grade and are commercially available.

[0109] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The HRTEM used was a JEM-2100 (Nippon Electron Ltd.), and the testing conditions were: accelerating voltage of 200 kV. The diameter of the boron-doped carbon nanocages was measured from the HRTEM images.

[0110] The pore structure properties of the material were detected using the BET test method. Specifically, a Quantachrome AS-6B analyzer was used for the determination, and the mesopore distribution curve was calculated from the desorption curve using the Barrett-Joyner-Halenda (BJH) method.

[0111] The elemental composition of the material surface was determined by X-ray photoelectron spectroscopy (XPS). X-ray photoelectron spectroscopy analysis was performed on an ESCALab250 X-ray photoelectron spectrometer from Thermo Scientific equipped with Thermo Avantage V5.926 software. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV and a power of 150 W. The narrow scan passthrough energy was 30 eV, and the baseline vacuum during analysis was 6.53 × 10⁻⁶. -9 mbar, electron binding energy was corrected using the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and quantitative analysis was performed using the sensitivity factor method in the analysis module.

[0112] The degree of graphitization of the material was characterized by Raman spectroscopy at 1355 cm⁻¹. -1 The peak (D peak) is attributed to structural defects, consisting of amorphous carbon, at 1585 cm⁻¹. -1 The peak (G peak) is attributed to carbon in a planar structure. I0 is typically used. D / I G The degree of graphitization of a material is characterized by the intensity ratio of the D peak to the G peak. D / I G The higher the value, the more defects and the lower the degree of graphitization. The Raman spectrum of the material was obtained using an RM2000 microconfocal Raman spectrometer (Reinshaw product). Technical specifications: The excitation source was a He-Ne laser with a wavelength of 525 nm.

[0113] ORR electrochemical performance testing was conducted using Solartron Analytical EnergyLab and Princeton Applied Research (Model 636A) instruments. The methods and test conditions were as follows: The catalyst polarization curve (LSV) was measured at 1600 rpm in O2-saturated 0.1 M HClO4, and the electrochemical active area (ECSA) was measured in Ar-saturated 0.1 M HClO4. For stability testing, 5000 cycles were performed in O2-saturated 0.1 M HClO4 within the range of 0.6 V–0.95 V (vs. RHE), followed by testing LSV and ECSA using the same method. For all tests, the catalyst was prepared as a uniformly dispersed slurry and coated onto a 5 mm diameter glassy carbon electrode. The platinum content of the catalyst on the electrode was controlled within the range of 1–4 μg. No iR correction was performed in the calculations.

[0114] Preparation Example 1

[0115] This preparation example illustrates the preparation of carbon nanocages.

[0116] (1) Weigh 15g of basic nickel carbonate and 15g of citric acid, add them to a beaker containing 40mL of deionized water, stir and mix them evenly at 80℃, and continue to heat and evaporate to dryness to obtain a solid precursor.

[0117] (2) Place the precursor obtained in step (1) into a ceramic boat, then place the ceramic boat in the constant temperature zone of a tube furnace, introduce nitrogen gas with a flow rate of 80 mL / min, and heat it to 600℃ at a rate of 10℃ / min. After holding the temperature for 1 hour, continue to heat it to 900℃ at a rate of 10℃ / min and hold the temperature for 2 hours. Stop heating and cool it to room temperature under a nitrogen atmosphere to obtain the pyrolysis product.

[0118] (3) Add the pyrolysis product obtained in step (2) to an aqueous solution containing 2M hydrochloric acid and stir at 90°C for 8 hours. Then filter, collect the filtrate, wash with deionized water until the filtrate is neutral, and then dry the filter cake in a constant temperature oven at 120°C for 6 hours to obtain nano carbon cages.

[0119] TEM characterization of the carbon nanocages shows that the prepared material is a hollow cage-like carbon nanomaterial with a size of 5-30 nm.

[0120] The following examples illustrate boron-doped carbon nanocages and platinum-supported catalysts and their preparation.

[0121] Example A-1

[0122] Preparation of boron-doped carbon nanocages

[0123] Take 0.05 g of the carbon nanocage prepared in Preparation Example 1, add 0.14 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-doped carbon nanocages. Figure 1 The boron-doped carbon nanocage TEM obtained. Figure 2 XPS B1s image of the prepared boron-doped carbon nanocages. Figure 3 The pore size distribution curve of the boron-doped carbon nanocage (BJH) is shown. This material exhibits two mesopore distribution peaks at 3.24 nm and 17.40 nm, as determined by Raman spectroscopy. D / I G It is 0.89.

[0124] Preparation of platinum-supported catalysts

[0125] 0.06 g of boron-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added with stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The resulting mixture was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. Figure 4 This is a TEM image of the prepared platinum-supported catalyst.

[0126] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0127] Comparative Example 1

[0128] 0.06 g of the nano-carbon cage prepared in Preparation Example 1 was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to make the pH of the system 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. The platinum content in the catalyst is listed in Table 1.

[0129] Example A-2

[0130] Preparation of boron-doped carbon nanocages

[0131] Take 0.05 g of the carbon nanocage prepared in Preparation Example 1, add 0.21 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-doped carbon nanocages.

[0132] Preparation of platinum-supported catalysts

[0133] 0.06 g of boron-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0134] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0135] Example A-3

[0136] Preparation of boron-doped carbon nanocages

[0137] Take 0.05 g of the carbon nanocage prepared in Preparation Example 1, add 0.14 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 450 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-doped carbon nanocages.

[0138] Preparation of platinum-supported catalysts

[0139] 0.06 g of boron-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0140] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0141] Example A-4

[0142] Preparation of boron-doped carbon nanocages

[0143] Take 0.05 g of the carbon nanocage prepared in Preparation Example 1, add 0.05 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 1100℃ for 2 hours. The heating rate is 5℃ / min to obtain boron-doped carbon nanocages.

[0144] Preparation of platinum-supported catalysts

[0145] 0.06 g of boron-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0146] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0147] Example A-5 (Gas-supported Platinum)

[0148] The preparation of boron-doped carbon nanocages is the same as in Example A-1.

[0149] Preparation of platinum-supported catalysts

[0150] Take 0.05 g of boron-doped carbon nanocages, add 7.01 mL of chloroplatinic acid aqueous solution (1 g chloroplatinic acid / 100 mL aqueous solution), sonicate for 0.5 h, let stand for 48 h, and dry in a 60 °C oven for 12 h. Place the sample in a tube furnace and heat to 160 °C under a mixed atmosphere of nitrogen and hydrogen (hydrogen volume content 40%), and allow it to cool naturally after 1.5 h to obtain a boron-doped carbon nanocage-supported platinum catalyst.

[0151] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0152] Example A-6

[0153] Preparation of boron-doped carbon nanocages

[0154] Take 0.05 g of the carbon nanocage prepared in Preparation Example 1, add 0.06 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-doped carbon nanocages.

[0155] Preparation of platinum-supported catalysts

[0156] 0.06 g of boron-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0157] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0158] Preparation Example 2

[0159] This preparation example illustrates the preparation of nitrogen-containing carbon nanocages.

[0160] (1) Weigh 15g of basic nickel carbonate and 20.9g of ethylenediaminetetraacetic acid, add them to a beaker containing 40mL of deionized water, stir and mix them evenly at 80℃, and continue to heat and evaporate to dryness to obtain a solid precursor.

[0161] (2) Place the precursor obtained in step (1) into a ceramic boat, then place the ceramic boat in the constant temperature zone of a tube furnace, introduce nitrogen gas with a flow rate of 80 mL / min, and heat it to 600℃ at a rate of 10℃ / min. After holding the temperature for 1 hour, continue to heat it to 900℃ at a rate of 10℃ / min and hold the temperature for 2 hours. Stop heating and cool it to room temperature under a nitrogen atmosphere to obtain the pyrolysis product.

[0162] (3) Add the pyrolysis product obtained in step (2) to an aqueous solution containing 2M hydrochloric acid and stir at 90°C for 8 hours. Then filter, collect the filtrate, wash with deionized water until the filtrate is neutral, and then dry the filter cake in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-containing nano carbon cages.

[0163] TEM characterization of the carbon nanocages shows that the prepared material is a hollow cage-like carbon nanomaterial with a size of 5-20 nm.

[0164] The following examples illustrate boron-nitrogen co-doped carbon nanocages and platinum-supported catalysts and their preparation.

[0165] Example B-1

[0166] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0167] Take 0.05 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.28 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-nitrogen co-doped carbon nanocages. Figure 5 The boron-nitrogen co-doped nano-carbon cage TEM obtained. Figure 6 XPS B1s image of the boron-nitrogen co-doped nanocages. Figure 7 XPS N1s images of the prepared boron-nitrogen co-doped carbon nanocages show that, according to X-ray photoelectron spectroscopy, the molar percentages of pyrrole nitrogen and pyridine nitrogen on the surface of the boron-nitrogen co-doped carbon nanocages are 79.02%. Based on the total molar amount of nitrogen, X-ray photoelectron spectroscopy further shows that the molar percentages of pyrrole nitrogen on the surface of the boron-nitrogen co-doped carbon nanocages are 72.15% and pyridine nitrogen are 6.87%. Raman spectroscopy was used to determine I... D / I G The value is 0.76. Based on the BJH pore size distribution measured by BET, it can be found that the material has two mesopore distribution peaks at 4.73 nm and 18.62 nm.

[0168] (2) Preparation of platinum-supported catalysts

[0169] 0.06 g of boron-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added with stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The resulting mixture was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. Figure 8 This is a TEM image of the prepared platinum-supported catalyst.

[0170] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0171] Example B-2

[0172] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0173] 0.05 g of nitrogen-containing carbon nanocages prepared in Preparation Example 2 were added with 0.07 g of boric acid, ground for 5 minutes, and then calcined in an atmosphere furnace at 1100 °C for 2 hours. The heating rate was 5 °C / min, resulting in boron-nitrogen co-doped carbon nanocages. X-ray photoelectron spectroscopy (XPS) showed that the molar percentage of pyrrole nitrogen and pyridine nitrogen on the surface of the boron-nitrogen co-doped carbon nanocages was 84.44%. Based on the total molar amount of nitrogen, XPS showed that the molar percentage of pyrrole nitrogen on the surface of the boron-nitrogen co-doped carbon nanocages was 74.06%, and the molar percentage of pyridine nitrogen was 10.38%.

[0174] (2) Preparation of platinum-supported catalysts

[0175] 0.06 g of boron-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0176] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0177] Example B-3

[0178] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0179] Take 0.05 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.07 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-nitrogen co-doped carbon nanocages.

[0180] (2) Preparation of platinum-supported catalysts

[0181] 0.06 g of boron-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0182] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0183] Example B-4

[0184] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0185] Take 0.05 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.14 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-nitrogen co-doped carbon nanocages.

[0186] (2) Preparation of platinum-supported catalysts

[0187] 0.06 g of boron-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0188] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0189] Example B-5

[0190] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0191] Take 0.05 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.14 g of boric acid, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain boron-nitrogen co-doped carbon nanocages.

[0192] (2) Preparation of platinum-supported catalysts

[0193] 0.06 g of boron-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.

[0194] The contents of each element in the boron-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.

[0195] Example B-6 (Gas-supported Platinum)

[0196] (1) Preparation of boron-nitrogen co-doped carbon nanocages

[0197] The same as in Example B-1, which describes the preparation of boron-nitrogen co-doped carbon nanocages.

[0198] (2) Preparation of platinum-supported catalysts

[0199] Take 0.05 g of boron-nitrogen co-doped carbon nanocages, add 7.01 mL of chloroplatinic acid aqueous solution (1 g chloroplatinic acid / 100 mL aqueous solution), sonicate for 0.5 h, let stand for 48 h, and dry in a constant temperature oven at 60 °C for 12 h. Place the sample in a tube furnace and heat to 160 °C under a mixed atmosphere of nitrogen and hydrogen (hydrogen volume content 40%), and allow it to cool naturally after 1.5 h to obtain a boron-nitrogen co-doped carbon nanocage platinum-supported catalyst.

[0200] The platinum content in the catalyst is listed in Table 1.

[0201] Table 1

[0202]

[0203]

[0204] The ORR performance of the platinum-supported catalysts prepared in the above examples and comparative examples is shown in Table 2 below.

[0205] Table 2

[0206]

[0207] As can be seen from the above data, the graphitized carbon nanocage containing boron provided by this invention significantly improves the catalytic activity when used as a support in fuel cell catalysts (Pt / C catalysts).

[0208] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A carbon-based catalyst containing platinum for use in fuel cells, characterized in that, The catalyst comprises a support and platinum supported on the support; the support is a graphitized carbon nanocage containing boron, the graphitized carbon nanocage containing boron having a hollow cage-like structure with a diameter of 2-100 nm, and the molar percentage of boron atoms measured by XPS is 15-30%; The graphitized carbon nanocage containing boron has two or more mesoporous distribution peaks; the first most probable pore size of the graphitized carbon nanocage containing boron is 2-5 nanometers, and the second most probable pore size is 10-30 nanometers.

2. The carbon-based catalyst containing platinum according to claim 1, wherein, The graphitized carbon nanocage containing boron has a hollow cage-like structure with a diameter of 2-50 nm.

3. The carbon-based catalyst containing platinum according to claim 2, wherein, The graphitized carbon nanocage containing boron has a hollow cage-like structure with a diameter of 5-30 nm.

4. The carbon-based catalyst containing platinum according to claim 1, wherein, In the Raman curve of the graphitized carbon nanocage containing boron, I D / I G The value is less than 1.

2.

5. The carbon-based catalyst containing platinum according to claim 4, wherein, In the Raman curve of the graphitized carbon nanocage containing boron, I D / I G The value is less than 1.

6. The carbon-based catalyst containing platinum according to claim 1, wherein, X-ray photoelectron spectroscopy revealed that the molar content of carbon on the surface of the graphitized carbon nanocage containing boron was 20-80%, the molar content of boron was 15-30%, and the molar content of oxygen was 5-50%.

7. The carbon-based catalyst containing platinum according to claim 1, wherein, The graphitized carbon nanocage containing boron also contains nitrogen, with a nitrogen atom molar percentage of 0.5-10% as measured by XPS.

8. The carbon-based catalyst containing platinum according to claim 7, wherein, X-ray photoelectron spectroscopy revealed that the molar content of carbon on the surface of the graphitized carbon nanocage containing boron was 20-80%, the molar content of nitrogen was 0.5-10%, the molar content of oxygen was 5-50%, and the molar content of boron was 15-30%.

9. The carbon-based catalyst containing platinum according to claim 8, wherein, X-ray photoelectron spectroscopy revealed that the molar content of carbon on the surface of the boron-containing graphitized carbon nanocage was 30-70%, the molar content of nitrogen was 0.5-2%, the molar content of oxygen was 15-40%, and the molar content of boron was 15-29%.

10. The carbon-based catalyst containing platinum according to claim 7, wherein, X-ray photoelectron spectroscopy showed that the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the boron-containing graphitized carbon nanocage was greater than 70%.

11. The carbon-based catalyst containing platinum according to claim 10, wherein, X-ray photoelectron spectroscopy showed that the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the boron-containing graphitized carbon nanocage was greater than 80%.

12. The carbon-based catalyst containing platinum according to claim 7, wherein, Based on the total molar amount of nitrogen, X-ray photoelectron spectroscopy determined that the molar content of pyrrole nitrogen in the surface of the boron-containing graphitized carbon nanocage was 70-100%, and the molar content of pyridine nitrogen was 0-30%.

13. The carbon-based catalyst containing platinum according to claim 1, wherein, The preparation method of the graphitized carbon nanocage containing boron includes the following steps: (1) Provide a solution containing a transition metal salt, a carbon source and a solvent, and then dry it to obtain a precursor; (2) Under an inert or reducing atmosphere, the precursor obtained in step (1) is subjected to high-temperature pyrolysis at a temperature of 850-1300℃ to obtain pyrolysis products. The temperature is raised to the high-temperature pyrolysis temperature using a two-stage heating method; (3) The pyrolysis product is acid washed, and then solid-liquid separation and drying are performed to obtain nano-carbon cages; (4) The nano carbon cage is mixed with a boron source and then subjected to high temperature treatment at 300-1500℃.

14. The carbon-based catalyst containing platinum according to claim 13, wherein, In step (1), The carbon source is a nitrogen-free organic polybasic acid and / or a nitrogen-containing carbon source; And / or, the transition metal salt is selected from at least one of the organic acid salts, carbonates and basic carbonates of transition metals; And / or, the transition metal is at least one of iron, cobalt, nickel and copper; And / or, the molar ratio of the transition metal salt to the carbon source, calculated as a transition metal element, is 1:0.5-1; And / or, the solvent is water.

15. The carbon-based catalyst containing platinum according to claim 14, wherein, In step (1), The nitrogen-free organic polyacid is at least one of citric acid, maleic acid, pyromellitic acid, terephthalic acid, and malic acid; the nitrogen-containing carbon source is ethylenediaminetetraacetic acid. And / or, the organic acid salt of the transition metal is an organic carboxylate salt of the transition metal that does not contain heteroatoms; And / or, the transition metal is nickel; And / or, the molar ratio of the transition metal salt to the carbon source, calculated as a transition metal element, is 1:0.6-0.

9.

16. The carbon-based catalyst containing platinum according to claim 15, wherein, In step (1), The nitrogen-free organic polyacid is citric acid; And / or, the organic acid salt of the transition metal is an acetate.

17. The carbon-based catalyst containing platinum according to claim 13, wherein, In step (2), The high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 0.5-30℃ / min, and then maintaining a constant temperature; And / or, the isothermal time is 20-600 min; And / or, the temperature of the high-temperature pyrolysis is 850-1200℃; And / or, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; And / or, the reducing atmosphere is provided by hydrogen and optionally an inert gas.

18. The carbon-based catalyst containing platinum according to claim 17, wherein, The high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 1-20℃ / min, and then maintaining a constant temperature; And / or, the isothermal time is 60-480 min.

19. The carbon-based catalyst containing platinum according to claim 18, wherein, The high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 5-10℃ / min, and then maintaining a constant temperature.

20. The carbon-based catalyst containing platinum according to claim 13, wherein, In step (3), The pickling agent used to pickle the pyrolysis products is an aqueous solution of inorganic acid and / or an aqueous solution of organic acid; And / or, the pH value of the inorganic acid aqueous solution or the organic acid aqueous solution is less than 7; And / or, the pickling temperature is 20-120℃; the time is 0.1-48h.

21. The carbon-based catalyst containing platinum according to claim 20, wherein, The pickling agent used to acid wash the pyrolysis products is at least one of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution and citric acid aqueous solution; And / or, the pickling temperature is 60-100℃; the time is 4-12h.

22. The carbon-based catalyst containing platinum according to claim 21, wherein, The acid washing agent used to acid wash the pyrolysis products is an aqueous solution of hydrochloric acid.

23. The carbon-based catalyst containing platinum according to claim 13, wherein, In step (4), The high-temperature treatment temperature is 400-1200℃; And / or, the high-temperature treatment time is 30-300 min; And / or, the boron source is selected from at least one of boric acid, boron oxide, ammonium borate, and ammonium hydrogen borate; And / or, the amount of the nano-carbon cage and the boron source is such that the boron-containing graphitized nano-carbon cage is prepared with a boron atom molar percentage content measured by XPS of 15-30%.

24. The carbon-based catalyst containing platinum according to claim 1, wherein, Based on the total amount of the carbon-based catalyst, the platinum mass percentage is 0.1-70%.

25. The carbon-based catalyst containing platinum according to claim 24, wherein, Based on the total amount of the carbon-based catalyst, the platinum mass percentage is 0.5-70%.

26. A method for preparing a platinum-containing carbon-based catalyst for a fuel cell according to any one of claims 1-25, the method comprising: After mixing the support with the platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction or gas-phase reduction. The carrier contains graphitized carbon nanocages containing boron.

27. The preparation method according to claim 26, wherein, The amount of support and platinum source used is such that, based on the total amount of the carbon-based catalyst, the mass percentage of platinum in the prepared catalyst is 0.1-70%.

28. The preparation method according to claim 27, wherein, The amount of support and platinum source used is such that, based on the total amount of the carbon-based catalyst, the mass percentage of platinum in the prepared catalyst is 0.5-70%.

29. The preparation method according to claim 26, wherein, After mixing the support and platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction, including: The support and platinum source were mixed in the presence of a solvent, the pH was adjusted, a reducing agent was added for reduction, and then dried to obtain a carbon-based catalyst containing metallic platinum.

30. The preparation method according to claim 29, wherein, Adjust the pH to 8-12.

31. The preparation method according to claim 29, wherein, The platinum source is selected from at least one of chloroplatinic acid, potassium chloroplatinate, and sodium chloroplatinate; and / or the concentration of the platinum source is 0.5-5 mol / L.

32. The preparation method according to claim 29, wherein, The reducing agent is selected from one or more of citric acid, ascorbic acid, formaldehyde, formic acid, ethylene glycol, sodium citrate, hydrazine hydrate, sodium borohydride, and glycerol.

33. The preparation method according to claim 29, wherein, The molar ratio of the reducing agent to the platinum source (calculated as Pt) is 2-100.

34. The preparation method according to claim 29, wherein, The reduction temperature is 50-150℃, and the reduction time is 2-15h.

35. The preparation method according to claim 26, wherein, After mixing the support and platinum source in the presence of a solvent, carbon-based catalysts containing metallic platinum are obtained by gas-phase reduction, including: The carrier and platinum source are mixed in the presence of a solvent, and the solvent is removed to obtain a precursor material. The precursor material is then heat-treated in a reducing atmosphere.

36. The preparation method according to claim 35, wherein, The precursor material is subjected to heat treatment at 80-300℃ for 1-4 hours.

37. The preparation method according to claim 35, wherein, The platinum source is selected from at least one of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate, and platinum acetylacetonate.

38. The preparation method according to claim 35, wherein, The solvent is one or more of water, alcohol solvents, and ketone solvents.

39. The preparation method according to claim 38, wherein, The solvent is water and / or ethanol.

40. The preparation method according to claim 35, wherein, Before removing the solvent, allow the mixed materials to stand.

41. The preparation method according to claim 40, wherein, The settling time is 15-24 hours.

42. The preparation method according to claim 35, wherein, The drying temperature during solvent removal is below 100℃.

43. The preparation method according to claim 35, wherein, The reducing atmosphere is provided by hydrogen and optionally an inert gas.

44. The preparation method according to claim 43, wherein, The reducing atmosphere is provided by a mixture of hydrogen and nitrogen.

45. The preparation method according to claim 44, wherein, The hydrogen content in the mixed atmosphere is 5-30% by volume.

Citation Information

Patent Citations

  • Preparation method of hollow carbon nanocage loaded platinum-based composite catalysts

    CN102600835A

  • Preparation method of boron and nitrogen co-doped hollow carbon nanocage

    CN104961119A

  • Methods for synthesizing carbon nanocages

    US20180257940A1